SEMIOTIC ANALYSIS OF THE LOVE MYSELF MESSAGE IN THE BTS SONG LYRICS 'EPIPHANY' - Larasati, Maria Fransiska; Daniar, Agus; Marta, Rustono Farady (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2022)
The song is one of the communication media that can spread messages. In a song lyric, there is a meaning to be conveyed from the creator and singer to the audience. This study determines the meaning of the message of love myself, raised by the South Korean boyband, BTS, through their song entitled Epiphany. 4 aspects of self-love must be met by someone to love oneself, namely self-awareness, self-worth, self-esteem, and self-care. This study examines whether the Epiphany song sung by BTS contains these four aspects of self-love. This research uses Ferdinand de Saussure's semiotic analysis method. The data were analyzed by determining the signifier and the signified in the lyrics of the Epiphany song. The findings show that the song Epiphany lyrics contain four self-love aspects. Self-awareness is a person's awareness that comes from the individual's thought process. The song's lyrics describe how a person begins to realize and begins to ask himself that his attitude in living life is not as it should be. The next stage is self-worth, when a person has confidence in himself. The lyrics of the song, it is described the emergence of awareness that he is valuable regardless of the shortcomings he has. The third stage of self-love is self-esteem, where an individual feels satisfied with himself and comfortable with the conditions that exist in himself and his environment. In the song lyrics, it is described that a person is aware of loving himself and accepting himself as he is. The self-care stage is the last stage where in the song lyrics, it is described that a person must take care of themselves by not hurting themselves physically and psychologically To cite this article (7th APA style): Larasati, M. F., Daniar, A., & Marta, R. F. (2022). Semiotic analysis of the love myself message in the BTS song lyrics "epiphany". Journal Communication Spectrum: Capturing New Perspectives in Communication 12(1), 68-76. https://doi.org/10.36782/jcs.v12i1.2183